PHONEMIC CHART MEDIA: TO IMPROVE THE STUDENTS’ PRONUNCIATION ON THE SECOND SEMESTER STKIP PGRI BANGKALAN (A CLASSROOM ACTION RESEARCH ) - Chairuddin, Chairuddin (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2017)
The purpose of this article is to examine the pronunciation of the students in speaking class through phonemic chart media. The findings from this report measure that most of students had difficulties in the correct sound symbol, stress, rhythm, and intonation. More specifically, the results showed that the difficulties affected by many factors such as lack of practicing, listening, imitating, and teaching learning process by the lecturer causes the students felt bored because the teaching learning process seemed to be monotonous. These findings suggest that phonemic chart is one of solution in solving the problem of students’ pronunciation. The researcher believes this chart became a good media for students in enhancing their pronunciation ability and also to make the enjoyable situation in teaching learning process. In this research, the researcher used a classroom action research in which the setting was conducted in STKIP PGRI Bangkalan which involves one class of second semester students.